Gender, genetics, translation: Encounters in the Feminist Translator’s Archive of Barbara Godard - Karpinski, Eva C. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
The article demonstrates the usefulness of textual genetics in corroborating the dynamic, process-oriented concepts of translation developed by feminist translation theorists. Focusing on the Canadian scholar and translator Barbara Godard, the paper examines her translation manuscripts of Nicole Brossard’s L’Amèr: ou le chapitre effrité (1977) and Amantes (1980), published in English as These Our Mothers (1983) and Lovhers (1986). The author argues that genetic analysis has the potential to challenge conventional understandings of translation as a linear transfer of meaning in the exchange of equivalences and that genetics can supply evidence that translation is a multidirectional, recursive and dialogical process of thought and transformation, a creative combination rather than a transparent substitution of meaning. The graphic markings, layerings, and inscriptions on the archival drafts reveal complex intersubjective and interdiscursive foldings at the heart of translation and expose translation as a series of temporal re-readings. They bring into view different encounters and relationalities and reaffirm the view of translation as a cultivation of friendship and collaboration.